2023
DOI: 10.1038/s41698-023-00441-5
|View full text |Cite
|
Sign up to set email alerts
|

High risk clear cell renal cell carcinoma microenvironments contain protumour immunophenotypes lacking specific immune checkpoints

Arti M. Raghubar,
Nicholas A. Matigian,
Joanna Crawford
et al.

Abstract: Perioperative immune checkpoint inhibitor (ICI) trials for intermediate high-risk clear cell renal cell carcinoma (ccRCC) have failed to consistently demonstrate improved patient outcomes. These unsuccessful ICI trials suggest that the tumour infiltrating immunophenotypes, termed here as the immune cell types, states and their spatial location within the tumour microenvironment (TME), were unfavourable for ICI treatment. Defining the tumour infiltrating immune cells may assist with the identification of predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…However, a notable proportion of patients experience disease progression shortly after initiating systemic treatment. Additionally, outcomes from adjuvant ICI trials for localized ccRCC have not shown improvements in survival ( Raghubar et al, 2023 ). These unsuccessful trials suggest that the types, states, and spatial distribution of tumor-infiltrating immune cells within the TME may not favor ICI treatment.…”
Section: Current Microphysiological Systems Of ‘Cold’ Tumorsmentioning
confidence: 99%
“…However, a notable proportion of patients experience disease progression shortly after initiating systemic treatment. Additionally, outcomes from adjuvant ICI trials for localized ccRCC have not shown improvements in survival ( Raghubar et al, 2023 ). These unsuccessful trials suggest that the types, states, and spatial distribution of tumor-infiltrating immune cells within the TME may not favor ICI treatment.…”
Section: Current Microphysiological Systems Of ‘Cold’ Tumorsmentioning
confidence: 99%
“… (Davidson et al 2023 ) Renal cell carcinoma Visium 6 patients, 10 samples Mechanisms explaining lack of response to immunotherapy in high-risk patients, including exhausted immune cells and lack of expression of PD-1 , PD-L1 and CTLA4 genes. (Raghubar et al 2023 ) Prostate cancer GeoMx DSP Tissue microarray (TMA) TMA constructed from 27 patients, in total, 168 tumor cores from 56 tumors used. Metastatic prostate cancer immune infiltrate lacks PD1, PD-L1 and CTLA4 .…”
Section: Spatial Transcriptomics In Solid Tumors: What We’ve Learned ...mentioning
confidence: 99%
“…Kidney cancer is known to be responsive to immunotherapy, and spatial analysis has revealed that the underlying mechanisms may include myofibroblastic cancer-associated fibroblasts (myCAFs) (Davidson et al 2023 ). Elucidating the immune phenotype of high-risk clear cell renal cell carcinoma (ccRCC) with ST has also provided insights into the immunogenic TME of tumors that have abundant exhausted/pro-tumor immune cells and provided clues to mechanisms explaining the infrequent lack of response to immunotherapy, including exhausted immune cells and lack of expression of the PD-1 , PD-L1 and CTLA4 genes (Raghubar et al 2023 ).…”
Section: Spatial Transcriptomics In Solid Tumors: What We’ve Learned ...mentioning
confidence: 99%
“…Research has analyzed the TME of intermediate- to high-risk ccRCC patients using spatial transcriptome sequencing (ST-seq) and found that a high-level TME is rich in exhausted/pro-tumor immune cells and lacks specific checkpoint gene expression, suggesting its immunogenicity but unfavorable response to ICIs therapy. The types and status of immune cells infiltrating tumors may help predict responses to ICI therapy [ 133 ]. In ccRCC patients responding to ICI therapy, higher densities of tumor-infiltrating T cells, CTLs, and PD1-positive immune cells are observed [ 134 ].…”
Section: Predictive and Resistance Factors For Pd1/pd-l1 Inhibition I...mentioning
confidence: 99%